Transmission of Hepatitis B and C Virus Infection Through Body Piercing: A Systematic Review and Meta-Analysis. Issue 47 (November 2015) - Yang, Shigui; Wang, Dan; Zhang, Yuelun; Yu, Chengbo; Ren, Jingjing; Xu, Kaijin; Deng, Min; Tian, Guo; Ding, Cheng; Cao, Qing; Li, Yiping; Chen, Ping; et al.
Abstract : Abstract: Hepatitis B and hepatitis C are 2 types of potentially life-threatening liver diseases with high infection rate. Body piercing represents a progressively popular sociocultural phenomenon which is also a potential exposure approach for hepatitis B virus (HBV) and hepatitis C virus (HCV). Conclusions from those researches with statistically risk assessment of body piercing on HBV and HCV transmission are contradictory. Systematically analyze the association between body piercing and the risk of transmitting hepatitis B virus and hepatitis C virus for general population. Make evidence-based recommendations to the current practice and wake up public awareness of this health-threatening behavior. Comprehensive and high sensitivity search strategies were performed to exhaustively search related studies before 15 January 2015 (MEDLINE, EMBASE, WANFANG, CNKI datasets for published literatures, and Google and Google scholars for related grey articles). Two authors identified relevant studies for the review, abstracted data, and assessed literature quality independently and critically according to the selection criteria and quality assessment standard. Odds ratio (OR) and corresponding 95% confidence interval (CI) were used to estimate risk of HBV and HCV infection in relation to body piercing status. Subgroup analysis and sensitivity analysis were conducted to examine the source of heterogeneity and test the robust of the results. A total of 40 studies were included in this systematic review (10 for Hep-B, 26 for Hep-C, 4 for both Hep-B and Hep-C), the pooled OR (95% CI) for the association between body piercing and transmission of HBV/HCV is 1.80 (1.18, 2.75) and 1.83 (1.27, 2.64), respectively. Subgroup analysis suggested that highest risk of body piercing related to hepatitis C infection was for former soccer and veterans with OR of 4.63 (2.65, 8.10), while strongest association between body piercing and hepatitis B was for samples derived from students/community with OR of 2.40 (1.44, 4.02). The current systematic review and meta-analysis suggests that body piercing is significantly associated with the transmission of HBV as well as HCV, having body piercing probably can increase the risk of getting infected. Evidence from this study strongly recommends that comprehensive and effective programs should be established to provide safer piercing practice. Abstract : Supplemental Digital Content is available in the text